Strategi Perbaikan Tanggul Jebol di Aceh Tamiang - Revida, Erika; Rifa’i, Ahmad; Rizky, Mhd. Dhiya; Vaneysha, Vini (Jayapangus Press, 2024)
Floods are hydrometeorological disasters that most frequently occur in various regions of Indonesia, including the Aceh Tamiang Regency area. Floods in Aceh Tamiang Regency usually occur at the end of every year and result in obstacles to government programs and economic growth and disrupt daily community activities. Apart from that, the flood disaster also caused the embankment to break, as is the phenomenon that occurred in the Aceh Tamiang Regency area. This research aims to find out what strategies are used to repair broken embankments in Aceh Tamiang. The type of research used is qualitative. Data collection techniques in this research are interviews, observation and documentation. Meanwhile, the data analysis technique in this research is the SWOT analysis technique. The results of this research were that the strategy for repairing the broken embankment in Aceh Tamiang was carried out by (Pj) Regent Meurah Budiman lobbying for the budget from the Aceh Provincial Government and the central government to immediately repair the broken embankment, coordinating directly with the Aceh Government and the Center regarding the repair of the broken embankment. as well as normalizing the embankments with the help of local community self-help. The conclusion of this research is the strategy implemented by the local government regarding the embankment breach in Aceh Tamiang, namely building permanent embankments to prevent the same incident from recurring, carrying out regular monitoring of the embankments, if damage occurs to the embankments, repairs can be carried out immediately to avoid a recurrence of similar incidents.